2020
DOI: 10.1080/14702541.2020.1834335
|View full text |Cite
|
Sign up to set email alerts
|

Climate change, marginalised communities and considered debate within Scotland’s climate emergency

Abstract: The announcement by the Scottish Government of a global 'climate emergency' in May 2019, and the selection of Glasgow as the host city for the main COP26 talks to be held in late 2021 has helped focus attention to the impact of climate change in Scotland. The COVID-19 pandemic has also brought into sharp focus the disproportionate effect that shocks and stresses have on already vulnerable people and places. This short communication aims to contribute to these debates by clarifying existing strengths and open i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Discussing the need to reduce societal inequalities has been a common focus area in analogies between the pandemic and the climate crisis. The pandemic has demonstrated that the poor, women, elderly, and marginalised groups, are more vulnerable to disasters (Lee et al, 2020;Mabon et al, 2020), highlighting the need for prioritising efforts on enhancing climate justice to ensure a better response to climate-induced adverse events that are highly likely to occur in the future.…”
Section: Results Of the Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Discussing the need to reduce societal inequalities has been a common focus area in analogies between the pandemic and the climate crisis. The pandemic has demonstrated that the poor, women, elderly, and marginalised groups, are more vulnerable to disasters (Lee et al, 2020;Mabon et al, 2020), highlighting the need for prioritising efforts on enhancing climate justice to ensure a better response to climate-induced adverse events that are highly likely to occur in the future.…”
Section: Results Of the Bibliometric Analysismentioning
confidence: 99%
“…The pandemic accentuates the relevance of the SDGs 1 "No Poverty" and 13 "Climate Action" (UN, 2021) due to the social inequalities and the disaster-prone vulnerable groups (Lee et al, 2020;Mabon et al, 2020).…”
Section: Discussionmentioning
confidence: 99%